PENGARUH FAKTOR SOCIAL DEMOGHRAFIC, PERSONAL ATTITUDE, DAN CONTEXTUAL TERHADAP ENTREPRENEURIAL INTENTION DI KALANGAN MAHASISWA PERGURUAN TINGGI SWASTA DI KOTA MATARAM - Satriawan Satriawan; Topan Siswanto (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2022)
This study aims to determine the partial and simultaneous significant effect of social demographic, personal attitude, and contextual variables on Entrepreneurial Intention among Private Higher Education Students in Mataram City. This type of research is quantitative research with an associative approach. The data collection method used a questionnaire with a Likert scale. the sampling technique uses purposive sampling, with the sample criteria being students who have received entrepreneurship courses. The number of samples is 100 respondents. Data analysis uses multiple linear regression analysis techniques. The results showed that there was a positive and significant influence between social demographic variables, personal attitude towards Entrepreneurial Intention, and there was no positive and significant effect between contextual variables on Entrepreneurial Intention. Judging from the beta coefficient (β) that the variable that has the dominant influence is the Personal Attitude variable. The amount of the effective contribution (R Square) for each social demographic, personal attitude, and contextual variables to the Entrepreneurial Intention variable. by 51.3% the remaining 48.7% is influenced by other variables that are not examined in this study